Large-scale parameter modelling for millimeter-wave multiple-input multiple-output channel in 5G ultra-dense network - Olabode Idowu-Bismark; Francis Idachaba; Aderemi A. Atayero (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Network densification (ND) in 5G has been suggested as a solution to improve network capacity. ND has small cell backhaul as its bottleneck in the ensuing ultra-dense network (UDN). Due to the new deployment scenarios of small cells, it becomes necessary to thoroughly investigate the radio-propagation characteristics of the new transmission path between the base station and the small cells. The problem of the impact of small cell height on the backhaul large-scale parameters under typical outdoor-to-indoor (high-rise) and outdoor-to-outdoor (street canyon) scenarios was first investigated. Next, the probability distribution functions of the various parameters were investigated and modeled. Novel use of 5G NR air interface using a deterministic ray-tracing engine to characterize the backhaul at 28 GHz center frequency and 100 MHz bandwidth using 4x4 cross-polarized uniform planar array (UPA) at the base station and 2x2 multiple input, multiple output (MIMO) antennas at the small cells was proposed. New sets of models for root mean square (RMS) delay spread and RMS angular spread suitable for predicting network deployment in the two scenarios and similar environments were presented.